Revision of the thamnocephalid Genus Phallocryptus (Crustacea; Branchiopoda; Anostraca) - Rogers, D. Christopher (Zootaxa, 2003)
The family Thamnocephalidae and the genus Phallocryptus are defined using modern standards in anostracan taxonomy. The genus Phallocryptus is revised to include three species. Two species formerly considered as Branchinella (B. spinosa and B. sublettei), are demonstrated to have the same basic genital morphology as Phallocryptus wrighti (Smirnov). Phallocryptus has a distribution that suggests that this genus originated sometime in the Paleozoic. A key to the species of Phallocryptus is presented, and the family Thamnocephalidae is redefined.